Urban Resilience: Store Location Dynamics and Cultural Heritage - Mark van Duijn; Jan Rouwendal; Ruben van Loon (European Regional Science Association (ERSA), 2014)
In this paper we study the relationship between cultural heritage and retail store dynamics at the neighbourhood level in the Netherlands. We analyze the total number of stores, number of vacant stores and number of stores by retail sub-industry in neighbourhoods, thereby focusing on the impact of cultural heritage, while controlling for many other factors. We test whether the presence of cultural heritage has a causal impact on the retail activity in neighbourhoods using an instrumental variables strategy for cross-section data. We also compare the development of the various indicators of retail activity over time in neighbourhoods with and without cultural heritage to investigate a the existence of an impact of historical districts and buildings on urban resilience. We use a unique panel dataset from Locatus which has information on the location and type of stores in the Netherlands over a period of 7 years (2004-2010). The results show that the presence of cultural heritage increases the demand for shopping areas. Therefore, there are more stores in neighbourhoods where cultural heritage is present. We also show that the impact of cultural heritage and distance to the city centre for retail activity slowly changes over time, indicating a continuously changing urban environment. Furthermore, we provide evidence on the resilience of stores within cultural-rich neighbourhoods after the recession started in 2007 using a duration analysis.
Keywords: L81; R12; R33; Z1; 330